Global Population in Transition - Martins, Jo. M. (Springer International Publishing, 2018)
This book deals with macro and micro aspects of population change and their inter-face with socio-economic factors and impact. It examines theoretical notions and pursues their empirical manifestations and uses multidisciplinary approaches to population change and diversity. It investigates the organic nature of the relationships between socio-economic factors and population change and the feedback loops that affect so-cio-economic organisation and behaviour. The book brings together material often scattered in a number of sources and disciplines that helps to understand population change and their socio-economic aspects. In addition to dealing with the more conventional factors in population dynamics in the form of fertility, mortality and migration, the book examines socio-economic forces that influence them. It discusses population evolving attributes that affect population characteristics and social and behaviour and impact on the environment. Further, it deals with social organisation and pathways that lead to different social and economic development and standards of living of diverse populations. .